Hydrogeochemical analysis Mishca River district Canary province of Victor Fajardo, Department of Ayacucho - Castañeda Zavaleta, Marko Eduardo (2013)
This study is focused on the hydro geochemical characteristics of Mishca river located at Victor Fajardo province, Ayacucho department.The geochemical dispersion in water shows metallic values of silver, lead and zinc belonging to the Pucará metallotect mine-ralization cycle. Observed metals in water association are explained as part of the natural dispersion in water.